Upaya Edukasi Pendidik Kristen Dalam Meningkatkan Toleransi Beragama Di NKRI Kepada Peserta Didik SMP Satap 2 Kuala Pembuang Desa Jahitan Kecamatan Seruyan Hilir, Kabupaten Seruyan, Provinsi Kalimantan Tengah - Didi Suparina (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
Indonesia is a country rich in culture, natural wealth, race,ethnicity and religion. With this wealth, the symbol of Bhinneka Tunggal Ika was created, which means that even thought we are different, we are still one. With this, educators collaborate in the school enviromment and in the wider community which has many differences in order to anticipate and overcome the widespread intolerance within the republic of Indonesia. The locus of this research was carried out at State Middle School (SMP) Santap 2 Kuala pembuang , aschool located in Jahitan Village, Seruyan Hilir District, Seruyan Regency, Central Kalimantan Province. This is the author’s place toprovide community service. This research activity was carried out using direct observation methods through surveys, interviews and education supported by literature studies, religious tolerance means appreciating, respecting and distinguishing between existing religions. In this regard, Charistian and non-Christian aducators pray to provide lots of education about tolerance so that they become patriotic indivuduals. Christian education plays an important role in making the Indonesian nation a harmonious country like the Lord Jesus taught about loving your neighbors. With real love, people will slowly get to know the person of Jesus, Indonesia is a multicultural country that has very abundant wealth in terms of natural wealth, ethnicity, race and even religion. Departed by making students able to accept the differences that exist in the school environment and the community of the Republic of Indonesia.